Monitoring Pesticide Watering On Plants Shallot Using Mosquitto Network (MQTT) Client-Server Network - Muhammad Yaafi Melindra; Hendrick Hendrick; Nadia Alfitri; Rahmat Rahmat (Politeknik Negeri Padang, 2023)
Shallots are one of the leading commodities in several regions in Indonesia. In the cultivation of shallot plants there are pests that can reduce the quality of shallots. Along with the times, and to overcome the problem of watering pesticides for shallot plants, an automation tool is designed to make it easier for farmers to water pesticides. The design of this tool uses the concept of Internet of Thing (IoT) where the application used is Node-RED with the MQTT protocol. The optimum humidity for the growth and development of shallot plants is 50-70%, so soil moisture sensors are used to measure soil moisture. Pesticide watering also looks at weather conditions such as rain. Therefore, the raindrop sensor is used to detect rain. From several trials that have been carried out, it produces one experimental result that shows soil moisture of 35% where weather conditions are not raining and, the relay is active to perform pesticide watering. This indicates that the pesticide watering of shallot plants using the MQTT client-server network is successful carried out.